Developing an organisation culture to facilitate radical innovation. (3rd November 2008) - McLaughlin, Patrick; Bessant, John; Smart, Palie
This research adopts an experimental, 'probe and learn', approach to innovation management and organisational development in a medium sized mature engineering company. It deploys a grounded participative methodology, within a 'live' new product development team to surface nine antecedents of a radical innovation culture. These emerging themes were triangulated using the established Organization Culture Assessment Instrument (OCAI) and the KEYS Creative Climate Assessment Tool. The aggregated data is discussed in terms of the different aspects of organisational culture and the distinct continuous and discontinuous cultural archetype forms. Finally 16 actionable management interventions were identified to promote radicalness. These were reviewed in the context of previous empirical case research and in dialogue within a UK Government Department of Trade and Industry forum to promote discontinuous innovation. The outcomes divulge a plan for change to assist the company's transition, through purposeful experimentation, between cultural archetypes and embed a radical innovation culture.